Geriatric Rehabilitation: A Family Practice Approach - Nixon, Murray (1989)
Geriatric patients require rehabilitative measures that restore function and prevent further loss, with the goal of preserving independence. Assessment of functional ability and problems contributing to the disability (there are frequently more than one in elderly patients) help to make realistic goals for treatment. Functional scales provide rational evaluation of baseline status, progress made during treatment, and when remission has occurred.